Conjugated small organic molecules: synthesis and characterization of 4-arylpyrazole-decorated dibenzothiophenes. (19th May 2020) - Panda, Satyajit; Jat, Ram Singh; Fayaz, Amir; Saha, Jony; Thirumoorthi, Ramalingam; Roy, Tapta Kanchan; Bhanuchandra, M.
Abstract : 4-Arylpyrazole-decorated dibenzothiophenes have been synthesized. Abstract : 4-Arylpyrazole-decorated dibenzothiophenes have been synthesized. The synthesis involves the treatment of 2, 8-dibromodibenzothiophene with pyrazole under Ullmann-type amination conditions for the dual C–N bond formation. The selective bromination of the resulting dual C–N bonded 2, 8-dipyrazolyldibenzothiophene, and the subsequent Suzuki–Miyaura reaction furnished the target conjugated materials comprising small organic molecules. The electron-deficient dibenzothiophene- S, S -dioxide core was obtained in quantitative yield. UV-Vis absorption studies indicated changes in the positions of the peak maxima upon increasing the conjugation length. Electrochemical and theoretical investigations of selected synthesized materials are also included.